Status dan Determinan Pendapatan Petani Agroforestri di Lingkungan Taman Nasional Gunung Ciremai - nFN Suyadi; nFN Sumardjo; Zaim Uchrowi; Prabowo Tjitropranoto; Dewa Ketut Sadra Swastika (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2018)
EnglishRural communities in Gunung Ciremai National Park (GCNP) are generally low income farmers. Farms that have long been adopted agroforestry farming systems through inter generation legacy. The existing agroforestry technology applied by the farmers remains the simple traditional technology, so that the crops yields and income are low. Understanding the determinants of farmers’ income is useful in formulating the appropriate policy for increasing farmers’ income. This study was aimed to analyze the level and determinants of the agroforestry farmers income in GCNP. This research was conducted in Kuningan and Majalengka Regency, West Java Province, in July to October 2017. The data was collected by interviewing 310 agroforestry farmers which were selected using the cluster random sampling technique with clusters consisted of the locations of farmer groups from agroforestry in the GCNP buffer zone. The data was analized using descriptive statistics and regression inferential statistics. The results show that the income of agroforestry farmers was low because of low agroforestry farmers’ capacity, weak extension support and weak leadership role of informal leaders. Supports of the forestry extension service and informal leaders' leadership roles are needed for enhancing the agroforestry farmers’ capacity in increasing their income.IndonesianMasyarakat perdesaan di lingkungan Taman Nasional Gunung Ciremai (TNGC) umumnya adalah petani kurang sejahtera yang telah lama menekuni agroforestri turun-temurun. Penerapan teknologi pada sistem usaha tani agroforestri masih sederhana sehingga produktivitas tanaman masih rendah yang berdampak pada rendahnya pendapatan. Berbagai faktor dapat memengaruhi tingkat pendapatan petani agroforestri, sehingga perlu diungkap faktor-faktor yang dapat meningkatkan atau menurunkan pendapatan petani. Penelitian ini bertujuan untuk menganalisis besaran dan determinan pendapatan petani agroforestri di lingkungan TNGC. Penelitian ini dilakukan di Kabupaten Kuningan dan Majalengka, Provinsi Jawa Barat pada bulan Juli sampai Oktober 2017. Data diperoleh dari 310 orang petani yang dipilih berdasarkan cluster random sampling dengan klaster lokasi kelompok tani agroforestri di desa penyangga kawasan TNGC. Data dianalisis menggunakan metode statistik deskriptif dan statistik inferensial regresi. Hasil penelitian menunjukkan bahwa pendapatan petani agroforestri di lingkungan TNGC rendah karena rendahnya kapasitas petani agroforestri, lemahnya dukungan penyuluhan kehutanan, dan lemahnya peran kepemimpinan tokoh informal. Dukungan penyuluhan kehutanan dan peran kepemimpinan tokoh informal perlu ditingkatkan agar petani agroforestri memiliki kapasitas yang memadai dalam meningkatkan pendapatan mereka.